Home delivery and newborn care practices among urban women in western Nepal: a questionnaire survey - Giri Sabitri; Sreekumaran Binu V; Joshi Hari S; Sreeramareddy Chandrashekhar T; Chuni Neena (BMC, 2006)
Abstract Background About 98% of newborn deaths occur in developing countries, where most newborns deaths occur at home. In Nepal, approximately, 90% of deliveries take place at home. Information about reasons for delivering at home and newborn care practices in urban areas of Nepal is lacking and such information will be useful for policy makers. Methods A cross-sectional survey was carried out in the immunisation clinics of Pokhara city, western Nepal during January and February, 2006. Two trained health workers administered a semi-structured questionnaire to the mothers who had delivered at home. Results A total of 240 mothers were interviewed. Planned home deliveries were 140 (58.3%) and 100 (41.7%) were unplanned. Only 6.2% of deliveries had a skilled birth attendant present and 38 (15.8%) mothers gave birth alone. Only 46 (16.2%) women had used a clean home delivery kit and only 92 (38.3%) birth attendants had washed their hands. The umbilical cord was cut after expulsion of placenta in 154 (64.2%) deliveries and cord was cut using a new/boiled blade in 217 (90.4%) deliveries. Mustard oil was applied to the umbilical cord in 53 (22.1%) deliveries. Birth place was heated throughout the delivery in 88 (64.2%) deliveries. Only 100 (45.8%) newborns were wrapped within 10 minutes and 233 (97.1%) were wrapped within 30 minutes. Majority (93.8%) of the newborns were given a bath soon after birth. Mustard oil massage of the newborns was a common practice (144, 60%). Sixteen (10.8%) mothers did not feed colostrum to their babies. Prelacteal feeds were given to 37(15.2%) newborns. Initiation rates of breast-feeding were 57.9% within one hour and 85.4% within 24 hours. Main reasons cited for delivering at home were 'preference' (25.7%), 'ease and convenience' (21.4%) for planned deliveries while 'precipitate labor' (51%), 'lack of transportation' (18%) and 'lack of escort' during labor (11%) were cited for the unplanned ones. Conclusion High-risk home delivery and newborn care practices are common in urban population also. In-depth qualitative studies are needed to explore the reasons for delivering at home. Community-based interventions are required to improve the number of families engaging a skilled attendant and hygiene during delivery. The high-risk traditional newborn care practices like delayed wrapping, bathing, mustard oil massage, prelacteal feeding and discarding colostrum need to be addressed by culturally acceptable community-based health education programmes.